Analisis Penambahan Warna Masterbatch 1%, 5% dan 15% Terhadap Kekuatan Tarik Material Plastik Polypropylene (PP) - Vita; Widjaja, Hartono (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2022)
Plastic has a very big role in everyday life, usually used for household needs, and in the automotive industry. One of the most widely used types of plastic is polypropylene (PP). Polypropylene (PP) has unique properties, flexibility, and a relatively low melting point that makes it stand out as an excellent material for a variety of applications such as ropes, hinge caps, food packaging, and the automotive industry. The addition of dyes to plastic materials can affect the good properties of plastics, one of which is tensile strength. In general, the addition of dye is given as much as 1 kg of granulated dye compared to 25 kg of plastic (4% granulated dye). This study aims to determine the tensile strength of polypropylene (PP) plastic material with the addition of 1%, 5% and 15% dye. So, it is necessary to test to assess the tensile strength which consists of 3 (three) components, namely: 1. Yield strength. 2. Maximum tensile strength and 3. Modulus of elasticity. The manufacture of product specimens uses the ASTM D638 standard and is made using the injection molding process. The values of yield strength, maximum tensile strength and modulus of elasticity on plastic materials without added dye were 30.02 N/mm2, 42.47 N/mm2 and 0.43 GPa. While the addition of dyes of 1%, 5% and 15% respectively the values are 1. Yield Strength of 32.53 N/mm2, 30.59 N/mm2 and 28.29 N/mm2, 2. Maximum tensile strength of 46.13 N/mm2, 45.33 N/mm2 and 41.57 N/mm2, 3. The elastic modulus are 0.58 GPa, 0.55 GPa and 0.42 GPa. The results showed an increase in the value of yield strength, maximum tensile strength and modulus of elasticity at the level of addition of 1% dye, but the value decreased with the addition of dye by 5% & 15%.